Appropriate standards of physical fitness of students - Larisa Lutsenko; Vjаcheslav Shuteev; Anastasija Sutula; Olga Sutula; Alfiya Deyneko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to establish the due norms and estimates of the level of development of physical fitness of students. Material & Methods: the assessment of physical fitness of students (young men) was carried out on the basis of the results, which are shown by them in tests: standing long-jump, run of 60 meters, run of 1000 meters, pull ups on a horizontal bar, trunk bending forward from sitting position, and shuttle run of 4х9 m. The selective method was used for the establishment of borders of the confidential interval. Results: results of the carried-out analysis showed that the level of physical fitness of students of NLA corresponds to the data, which are submitted in special literature. Conclusions: borders of the confidential interval for indicators of physical fitness of students of the general population, and also due standards and estimates of the level of development of their physical fitness are established on the basis of the received results.